The impact of westbound trans-meridian travel and intensified training on countermovement jump performance - Everett, K. L. A.; Chapman, D. W.; Mitchell, J. A.; Ball, N. (Journal of Australian Strength and Conditioning, 2017)
International long haul (>5h) air travel is a necessity for many highly trained athletes as part of their training or competition schedules. Negative effects associated with long haul travel may impair an athlete`s neuromuscular function. Countermovement jumps (CMJ) are frequently used to assess an athlete`s lower body neuromuscular status. This study assessed the impact of westbound trans-meridian travel and intensified training on changes in CMJ performance.